Innovative Demand Side Management Solutions Exploring Incentives and Barriers for Demand Side Management Solutions at Shared Charging Infrastructure Sites for Heavyweight Vehicles - Styff, Amanda; Thorell, Sara (My University, 2023)
A major part of the decarbonization efforts of society is related to the energy and transport sectors. The energy sector is undergoing a transition to renewable sources and at the same time Swedish electricity consumption is expected to double by 2045, resulting in two challenges. First, there is a problematic, daily and seasonal, mismatch between supply and demand due to intermittent renewable energy sources and fluctuating demand. Second, the required expansion and reinforcement of the grid is costly and may not be completed in time. When electrifying public transport, involved actors need to adopt new ways of working to address these future challenges in the energy system. Extending from the DREEMER-project, which includes stakeholders in public transportation and shared charging infrastructure, the thesis investigates the necessary incentives and potential barriers for actors to take a more active role in supporting the local electricity grid at bus charging sites. Furthermore, the thesis explores potential demand side management solutions and what measures actors could take to increase participation in the local energy system. The study began with a pre-study, followed by interviews with DREEMER-actors who recommended additional respondents. This led to another round of interviews with a technical focus. Simultaneously, a literature review on sharing economy concepts and technical solutions was conducted. Financial returns are identified as a necessary incentive, while environmental and social incentives are also recognized as important. The results highlight four main barriers that need to be overcome: lack of existing business models, regulatory barriers, uncertainty, and lack of knowledge. The potential of demand side management solutions is discussed in relation to the identified incentives and barriers.
Keywords: demand side management; charging infrastructure; sharing economy; business model; heavyweight transport; electrification; sustainable development